Khamir Cake with Sweetener Variations as a Potential Snack for People with Type II Diabetes Mellitus - Dina Fatimah; Yunda Maymanah Rahmadewi; Cita Eri Ayuningtyas (Bulletin of Culinary Art and Hospitality, 2023)
Khamir is a traditional cake mostly found in Pemalang City, Central Java, Indonesia. This cake was an acculturation product from Arab and Pemalang cultures, so this cake is commonly consumed by people of Pemalang and Arabic descent. Khamir cake is made primarily from a large quantity of wheat flour and sugar. Due to its high sugar content, people with diabetes of history of diabetes are not suggested to consume this cake. This study aims to explore healthy food development (theoretical), produce khamir cake alternative for people with type II diabetes mellitus (practical), along with exploring consumers’ preferences for khamir cake made from brown sugar, honey, stevia sugar, and corn sugar (practical). This research was quantitative experiment research. We used a questionnaire as an instrument to gather the respondents’ preferences for the produced alternative khamir cake. In this study, we prepared khamir cake with the sugar variation from brown sugar, honey, stevia sugar, and corn sugar.